1983
DOI: 10.1002/ar.1092060308
|View full text |Cite
|
Sign up to set email alerts
|

Gross morphological analysis of limb regeneration in postmetamorphic adult Ambystoma

Abstract: Due to the great disparity between regeneration times for the larval salamander (40 days), axolotl (30+ days), newt (44 days), and adult salamander (155 to 370 days), a staging system was devised so correlative comparisons could be made between regenerative model systems. The sequence was based on two criteria: 1) the stages should be similar to previously reported sequences for the newt, axolotl, and larval salamander, and 2) the stages must be readily recognizable by examination of the external morphology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 12 publications
1
58
2
Order By: Relevance
“…The ability of axolotls to regenerate limbs independently of their metamorphic state has been demonstrated over three decades ago. 47 These experiments also demonstrate that regeneration is not dependent on an aquatic environment, as once metamorphosis is complete, axolotls are terrestrial, and they still regenerate. 47,48 More recently, Maden's group, in their skin woundhealing study, specifically addressed this point by inducing metamorphosis of adult axolotls and assessing skin regeneration/scar-free healing in pedomorphic versus metamorphic animals.…”
Section: Axolotl As a Model For Scarless Wound Healingmentioning
confidence: 79%
“…The ability of axolotls to regenerate limbs independently of their metamorphic state has been demonstrated over three decades ago. 47 These experiments also demonstrate that regeneration is not dependent on an aquatic environment, as once metamorphosis is complete, axolotls are terrestrial, and they still regenerate. 47,48 More recently, Maden's group, in their skin woundhealing study, specifically addressed this point by inducing metamorphosis of adult axolotls and assessing skin regeneration/scar-free healing in pedomorphic versus metamorphic animals.…”
Section: Axolotl As a Model For Scarless Wound Healingmentioning
confidence: 79%
“…We (Young, 1977a(Young, , 1977b(Young, , 1977c(Young, , 1983(Young, , 2000(Young, , 2004Young et al, 1983aYoung et al, , 1983bYoung et al, , 1983cYoung et al, , 1983dYoung et al, , 1985Young et al, , 1989aYoung et al, , 1989bYoung et al, , 1991Young et al, , 1992aYoung et al, , 1992bYoung et al, , 1993Young et al, , 1995Young et al, , 1998aYoung et al, , 1998bYoung et al, , 1999Young et al, , 2001aYoung et al, , 2001bYoung et al, , 2004aYoung et al, , 2004bLucas et al, 1993Lucas et al, , 1995Lucas et al, , 1996aLucas et al, , 1996bPate et al, 1993;Rogers et al, 1995;Dixson et al, 1996;Warejcka et al, 1996;Young and Lucas, 1998;Romero-Ramos et al, 2002) and others Jiang et al, 2002;Zhao et al, 2003) (see also Table 1) have observed that many tissues and organs contain a wide variety of precursor cells. The precursor cells observed include pluripotent epiblasticlike stem cells, pluripotent ectodermal stem cells, PPMSCs, and pluripotent endodermal stem cells; and multipotent, tripotent, bipotent, and unipotent progenitor cells.…”
Section: Differentation Of Pluripotent Stem Cells Vs Transdifferentimentioning
confidence: 99%
“…Therefore, every tissue within the body retains a complement of precursor cells denoted by its embryological origin. Based on previous and current studies by ourselves and others (Young, 1977a(Young, , 1977b(Young, , 1977c(Young, , 1983(Young, , 2000(Young, , 2004Young et al, 1983aYoung et al, , 1983bYoung et al, , 1983cYoung et al, , 1983dYoung et al, , 1985Young et al, , 1989aYoung et al, , 1989bYoung et al, , 1991Young et al, , 1992aYoung et al, , 1992bYoung et al, , 1993Young et al, , 1995Young et al, , 1998aYoung et al, , 1998bYoung et al, , 1999Young et al, , 2001aYoung et al, , 2001bYoung et al, , 2004aLucas et al, 1986Lucas et al, , 1992Lucas et al, , 1994aLucas et al, , 1994bLucas et al, , 1995Lucas, 1989;Bowerman et al, 1991;Caplan, 1991;Shoptaw et al, 1991;Gage et al, 1995;Grande et al, 1995;Saito et al, 1995;Cornelius et al, 1997;Eglitis and Mezey, 1997;Taylor et al, 1997;Ferrari et al, 1998;Young and Lucas, ...…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Urodele amphibians such as the axolotl and newt are unique in being able to regenerate their limbs throughout life, although the process is slower with advancing age of the animal. 34 Regeneration takes place in two major phases, the formation of a blastema that resembles the early limb bud, and the growth and differentiation of the blastema into the missing limb parts (Fig. 1).…”
Section: Amphibians As Models To Study Limb Regenerationmentioning
confidence: 99%